Scandinavian Legal Realism in Two Criminal Convictions of The Same Thing - Siti Munawaroh; Sri Mulyati; Suhendri Suhendri (Research Collaboration Community (RCC), 2022)
Human life is regulated and will never be separated from the provisions of binding regulations. Binding rules or norms in human life have the purpose of creating order, justice, and public welfare. The paradigm of legal positivism has always relied on the logic and validation of the ruler which makes people think that the ruler is the only law. This is strongly criticized by legal realists. The interesting thing about legal realism is the view that law must depart from the study of facts. American legal realism states that a judge decides something based on his personal preferences, and then makes a legal analysis to justify the expected outcome. This is different from legal realism in Scandinavia, which is based on logical positivism that developed in the modern era. Legal realism in Scandinavia intends to make legal science more scientific. Criticisms of legal realism include: legal realism presents the law only as a tool for resolving disputes on a case by case basis, there is no need for legal certainty because the approach is very casuistic so that judge’s understanding of cases can vary widely. Using legal studies approach, be expected that it can provide an overview of the problems that occur related to Scandinavian Legal Realism in the adultery case of SS with minors which is contrary to The Law of Number 35 of 2014 concerning Child Protection in conjunction with Article 65 Paragraph 1 of the Criminal Code. The judge's authority over the case is to give a verdict related to the SS case in accordance with positive law, the facts that actually happened, and the truth of the case that has been observed by the people involved and legal experts with the aim of maintaining order and protecting the community so that they always do the right thing.